Cross-Cultural Counseling as a Catalyst for Inclusivity in Implementing the Independent Curriculum in Schools - Budiyono, Alief; Yuslam, Yuslam (Asian Journal of Applied Education (AJAE), 2025)
Implementing the Independent Curriculum in schools presents challenges in creating an inclusive environment and accepting cultural diversity. One solution to overcome these challenges is through the application of cross-cultural counseling which can act as a catalyst for inclusivity. Cross-cultural counseling helps students understand, appreciate and respond to cultural differences in a positive way, thereby creating a harmonious school atmosphere and supporting their academic and social development. This research aims to explore the role of cross-cultural counseling in building multicultural awareness and its impact on student learning outcomes and behavior at school. The research method used was a qualitative approach with a descriptive design, where interviews were conducted with Counseling Guidance Teachers (BK) from MAN 1 and MAN 2 Banyumas. The research results show that cross-cultural counseling has a significant influence in increasing students' cultural awareness and encouraging them to appreciate diversity more. In addition, school counselors play a role in resolving intercultural conflicts, integrating inclusive values ​​in school programs, and providing academic assistance that is sensitive to students' culture. Evaluations of the impact of cross-cultural counseling have also shown improvements in learning outcomes, student engagement, and reductions in negative behaviors related to cultural differences. Overall, this research concludes that cross-cultural counseling plays an important role in supporting the implementation of the Independent Curriculum and creating an inclusive school environment.